The development of an in-situ biopolymer-based floating gel for the oral delivery of metformin hydrochloride - Ruedeekorn Wiwattanapatapee; Kalayamas Klabklay; Nontawat Raksajit; Worrawee Siripruekpong; Nattawut Leelakanok; Arpa Petchsomrit (Heliyon, 2023)
Diabetes remains a global public health threat because of its increasing prevalence and mortality, especially in people under the age of 25. Metformin hydrochloride (HCl), as recommended by American Diabetes Association in 2022, is the first-line therapy for type 2 diabetes in adults. Metformin has low oral bioavailability due to poor permeability. Therefore, by developing metformin HCl oral in situ gel, sustained delivery of metformin can be achieved, thus enhancing the absorption of the drug. Sodium alginate and pectin were used for formulating the system. Different adjuvant polymers, including HPMC K4M, HPMC K100 LV, PEG 4000, and SCMC were used as released-pattern-modifying agents. All formulations could afloat in 0.1 N HCl at the pH of 1.2 within a minute and stay afloat for over 8 h. The optimized formulation could be made from either sodium alginate (2%) and HPMC K4M (0.5%) or pectin (2%) and HPMC K4M (2%). The optimized formulations gradually released metformin HCl with a cumulative release of 80% within 8 h. We successfully developed floating in situ gels that can release metformin HCl sustainedly.